Pengembangan Media Pembelajaran Trainer Refrigerasi Kulkas 1 Pintu Mata Kuliah Praktik Teknik Pendingin dan Tata Udara - Nugraha, Gera; Suhendar, Suhendar; Irwanto, Irwanto (Jurnal Pendidikan Teknik Elektro, 2025)
Education is a process to develop humanity, or often referred to as “humanizing humans.”. This research aims to develop learning media in the form of a 1-door refrigerator refrigeration trainer for the refrigeration and air conditioning engineering practice course at UNTIRTA's Electrical Engineering Vocational Education. To answer the problem of the knowledge of students who teach the course in recognizing the components of the electrical system, maintenance, and repair of a 1-door refrigerator. This research uses the Research and Development (R&D) method with the 4-D development model, which includes 4 stages, namely the definition stage (define), design (design), development (develop), and the last is dissemination (disseminate). Data were collected through interviews, observations, validation of media experts and material experts, as well as the responses of users of this learning media. The media feasibility test by the media expert validator obtained an average score of 75, while the material feasibility test validated by the material expert obtained an average score of 64. The user response gave an average score of 56 out of 20 respondents. This shows that the 1-door refrigerator refrigeration trainer learning media is in the category of being very feasible to use for learning refrigeration and air conditioning techniques.